Characterizing the optical property of plasmonic nanomaterial and use them to develop a tool for wastewater treatment - Islam, Md. Faqrul; Iqbal, Mehzabien; Rahman, Tasin; Abdullah, Abu Yousha Mohammad (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.